P3 6 Extraterrestrial Wind Turbines - Which Planet Is Most Suitable - Miller, Tobias; Astrophel, Forseti; Simpson, Orlagh; Rodgers, Eliza (Physics Special Topics, 2023)
Wind power is a potentially essential form of sustainable energy, using the energy of wind to turn turbines and generate electricity. Wind turbines are usually found on the windiest places on Earth; however, there are windier places beyond Earth, in our own solar system. The winds of Neptune, for example, reach approximately 600 m/s, the fastest in the solar system. We find that the power generated by one turbine on Neptune is 235 GW, which means 13 Neptunian turbines are required to provide enough power for the world